2011
DOI: 10.5216/ree.v13i4.10949
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de bastonetes Gram-negativos isolados da saliva de trabalhadores da saúde

Abstract: Prevalência de bastonetes Gram-negativos isolados da saliva de trabalhadores da saúdePrevalence of Gram-negative

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
(22 reference statements)
0
5
0
2
Order By: Relevance
“…A similar study performed with 278 members of a healthcare team at a university hospital found a 69.6% colonization rate by gram-negative bacteria (GNB) (enterobacteria and/or non-fermenters) 20 . In studies with immunocompromised individuals, the presence of Enterobacteriaceae in the oral cavity varied from 32.5% to 60.7% 10 , 21 .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…A similar study performed with 278 members of a healthcare team at a university hospital found a 69.6% colonization rate by gram-negative bacteria (GNB) (enterobacteria and/or non-fermenters) 20 . In studies with immunocompromised individuals, the presence of Enterobacteriaceae in the oral cavity varied from 32.5% to 60.7% 10 , 21 .…”
Section: Discussionmentioning
confidence: 91%
“…Another concerning factor is that 9.1% of the carriers were colonized by different species of enterobacteria. In one study performed with the healthcare team of a teaching hospital, 49.2% of the workers were multicolonized by GNB 20 . The large microbial diversity of the oral cavity reflects, among other factors, the presence of the dental biofilm, which enables special conditions for survival and growth 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies of the oropharyngeal colonization of healthcare professionals by Pseudomonas spp. are scant and the relevance of these carriers should be enlightened 3 , 4 , 11 , 12 . This research aimed to determine the prevalence of oral colonization and the antimicrobial susceptibility of Pseudomonas spp.…”
mentioning
confidence: 99%
“…De acuerdo con la cadena epidemiológica de infección, gotículas de saliva cargadas de microorganismos virulentos pueden constituir una fuente de contaminación cruzada y, consecuentemente, provocar la colonización de pacientes y trabajadores. Dicho mecanismo condiciona la diseminación de tales agentes, tanto en el ambiente hospitalario como en la propia comunidad 12 . De este modo, identificar profesionales del área de salud colonizados por microorganismos se configura como un riesgo para la seguridad de los pacientes 13 .…”
Section: Discussionunclassified